2014
DOI: 10.1002/ijop.12036
|View full text |Cite
|
Sign up to set email alerts
|

Neuroscientific evidence for defensive avoidance of fear appeals

Abstract: Previous studies indicate that people respond defensively to threatening health information, especially when the information challenges self-relevant goals. The authors investigated whether reduced acceptance of self-relevant health risk information is already visible in early attention allocation processes. In two experimental studies, participants were watching high- and low-threat health commercials, and at the same time had to pay attention to specific odd auditory stimuli in a sequence of frequent auditor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 20 publications
2
40
1
1
Order By: Relevance
“…These findings are in line with marketing research, which suggests that negative emotions such as fear and disgust underlie the effectiveness of warnings 41–44. Although some neurophysiological data suggest gruesome images may elicit ‘defensive avoidance’,45 46 experimental and population-based studies have failed to detect any significant adverse outcomes from defensive reactions such as avoidance 47–49. Further, a recent study50 that examined the impact of cigarette warnings on quit attempts via mediational pathways found that avoidance behaviour actually increased the frequency of thinking about the harmful effects of smoking.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with marketing research, which suggests that negative emotions such as fear and disgust underlie the effectiveness of warnings 41–44. Although some neurophysiological data suggest gruesome images may elicit ‘defensive avoidance’,45 46 experimental and population-based studies have failed to detect any significant adverse outcomes from defensive reactions such as avoidance 47–49. Further, a recent study50 that examined the impact of cigarette warnings on quit attempts via mediational pathways found that avoidance behaviour actually increased the frequency of thinking about the harmful effects of smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Individual level Females are more persuaded by fear-based messages than males Lennon, Rentfro, and O'Leary (2010) and Samu and Bhatnagar (2008) The tendency to seek strong sensations/experiences weakens the persuasiveness of fear appeals Becheur, Dib, Merunka, and Valette-Florence (2008) Individuals with favourable attitudes to advertised behaviour more persuaded by fear appeals than those with less favourable attitude Jäger and Eisend (2013) Repeated exposure or familiarity with a behaviour reduces the persuasiveness of fear appeals Andrews et al (2014), Kessels et al (2014) and Kim et al (2014) Self-efficacy influences attitudes towards the advert and increases persuasiveness Manyiwa and Brennan (2012) Low-intensity fear-based appeals work better with high uncertainty-avoidant respondents than highintensity appeals Reardon, Miller, Foubert, Vida, and Rybina (2006) Individuals highly committed to the worldview of drinking alcohol are less responsive to death-based fear appeals than lesser appeals Shehryar and Hunt (2005) Individuals with children are more responsive to potential health threats Latour and Tanner (2003) Stronger experiences of fear increase persuasion Terblanche-Smit and Terblanche (2010) More influenced by fear appeals when discussed with friends than with strangers Samu and Bhatnagar (2008) (Continued ) …”
Section: Influences Persuasionmentioning
confidence: 99%
“…They serve the purpose of maintaining a selfimage despite obvious cause for emotional/psychological distress. Though defense mechanisms serve to help individuals to cope up with routine situations they are pathological if they are used to ignore the warning signs of something known to be harmful, or wrong (Bell, 1965;Abrams, 1968;Kessels et al, 2014).…”
Section: Figure 2 Reason For Contining Using Tobacco Despite Being Mmentioning
confidence: 99%